Juridical Analysis of Judges Decisions Regarding Termination of Employment Due to Presumed Absenteeism (Case Study of Supreme Court Decision Number 1242 K/PDT.SUS-PHI/2020) - Muhammad Alvin Naufal Rozaqul Hafidh,; Abdulovna, Daryna Dzemish (Indonesian Journal of Labour Law and Industrial Relations, 2024)
Abstract Yohanes Mansri Oncok as a former CV worker. Vita Permai who has worked for approximately 12 years, 5 months, 12 days. Yohanes Mansri Oncok was terminated by CV. Vita Permai. Due to the reason for applying for annual leave to CV. Vita Permai did not receive confirmation or response. The dispute occurred because Yohanes Mansri Oncok was considered absent by CV. Vita Permai and no compensation was given to Yohanes Mansri Oncok. There is also evidence that CV.Vita Permai does not regulate leave provisions in company regulations. As a legal step, Yohanes Mansri Oncok filed a lawsuit with PHI. In his considerations, the judge stated that Yohanes Mansri Oncok's lawsuit was rejected because he was declared absent, so it was rejected in its entirety. Yohanes Mansri Oncok submitted a cassation request to the Supreme Court and part of Yohanes Mansri Oncok's lawsuit was granted through Supreme Court dismissal Number 1242 K/Pdt.Sus-PHI/2020. This research aims to determine the legal relationship between Yohanes Mansri Oncok and CV. Vita Permai, as well as to find out the basis for the judge's consideration of not granting Yohanes Mansri Oncok's lawsuit request with CV. Vita Permai to get severance pay. The research method used is the legal relationship between Yohanes Mansri Oncok and CV. Vita Permai is a normative juridical type of legal research, on the basis that there is consideration of the starting point for research and analysis of legal regulations. Regarding Yohanes Mansri Oncok's status, he changed from being a worker who resigned due to absenteeism, becoming a worker who was laid off by CV. Vita Permai.